Evolutionary Game of Value Synergy in Industrial Chain: In the Context of “Chain Chief System” - Zhengang Zhang; Yushu Lu; Taiye Luo (Complexity)
The “chain chief system” is an institutional innovation that can enhance the responsibility of the industrial chain. Currently, various provinces and cities in China are adopting it to reap the benefits of resource combination. Traditional industrial synergy emphasizes “scale orientation,” and research on industrial policy, involving government administrative power, needs to be thoroughly discussed from the perspectives of government behavior and industry characteristics. This study utilizes the evolutionary game method to analyze the behavioral strategies of the government, leading enterprises, and other enterprises in the industrial chain under different conditions based on the perspective of value synergy. Relevant parameters of revenue and cost are modified for numerical simulation. The results demonstrate that the evolutionary stability strategy is influenced by various factors such as the government’s due diligence, subsidies, proportions allocated to different enterprises, benefits and costs, and industrial characteristics. Furthermore, the government can appropriately increase subsidies to leading enterprises and penalties for inaction, reduce barriers to data and scene sharing among enterprises in the industry, and lower industry concentration. These measures are more conducive to establish a “chain chief system” value synergy ecology in which all members actively participate.